131k views
3 votes
Solve for x. 25 - 3x = -5(1 - x) - 2x

User Phihag
by
6.2k points

2 Answers

4 votes

Answer:

5

Explanation:

First you would multiply -5 by everything in parenthesis so...

25 - 3x= -5 + 5x - 2x

Then 5x- 2x..

25 - 3x= -5 + 3x

Add -3x to both sides

25 = -5 + 6x

Add 5 to both side

30= 6x

Divide 6 on both side

5 = x

Hope this helped :)

User Kristian Frost
by
6.3k points
0 votes

Answer:


x = 5

Explanation:

25 - 3x = -5(1 - x) - 2x

We have to first get rid of the parenthesis:


-5 * 1 ==> -5


-5 * -x ==> 5x

So now you should have:

25 - 3x = -5 + 5x - 2x

Combine like terms:

25 - 3x = -5 + 5x - 2x

25 - 3x = -5 + 3x

Add 3x to both sides:

25 - 3x = -5 + 3x

+ 3x = + 3x

And you should have:

25 = -5 + 6x

Add 5 to both sides:

25 = -5 + 6x

+5 = +5

30 = 6x

Divide 6 to both sides:


(30)/(6) =
(6x)/(6)

5 = x

User Helloimyourmind
by
5.5k points